Kontekstualisasi Penafsiran Surat Al-Humazah di Era Disrupsi : Kajian Tafsir Tematik - Rahmad Fauzi; Fauzan AzimaSyafiuddin (Khulasah : Islamic Studies Journal, 2026)
This research examines the correlation between Surah Al-Humazah and the contemporary era of disruption. Bullying, which is detrimental, occurs in various contexts, including schools, workplaces, and the online world. Its impacts are detrimental to victims physically, psychologically, and emotionally. Prevention efforts require collaboration from various parties, including educational institutions, workplaces, communities, and parents. Demonstrating wisdom, patience, and engaging in constructive dialogue, as exemplified by Prophet Muhammad (PBUH), remains relevant in addressing bullying, even in the current era of disruption. Further research is needed to gain a deeper understanding of this issue, such as contextualizing the interpretation of Surah Al-Humazah in the era of disruption. The aim of this research is to examine Surah Al-Humazah in the context of the present time. The research method used is Library Research, employing a Qualitative Descriptive Analysis approach. Findings from this research indicate that Surah Al-Humazah condemns those who spread slander and mockery, affirming the concept of punishment in Hell for offenders. Although interpretations by scholars may vary, they all condemn negative behavior towards others. Hell is depicted as a destruction that reinforces the trait of arrogance. In the era of disruption, the analysis of this Surah emphasizes the importance of ethics in human interactions, particularly in the digitally influenced technological landscape. This Surah serves as a warning against negative behaviors such as defamation and slander, which are increasingly prevalent in contemporary times. The analysis of this Surah encompasses a deep understanding of the impact of negative behavior in the digital era, the social responsibility of leaders, information manipulation on social media platforms, and the psychological impact of such detrimental behavior. This Surah emphasizes the importance of values such as justice, integrity, and spiritual morality in everyday life. A profound understanding of Surah Al-Humazah can contribute to the creation of a more harmonious and fair society amidst the ongoing evolution of social dynamics.